Edukasi Peran Hak Asasi Manusia di Era Digital Lewat Filter Augmented Reality (AR) Instagram - Roman Aqviriyoso; Anung Rachman; Asmoro Nurhadi (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2022)
Human rights are the most basic rights owned by every individual around the world. In the digital era, human rights can also be called digital rights, which are human rights that guarantee that every citizen can access, use, create, and disseminate digital media. However, behind the role of Human Rights, there are also shortcomings where mutual respect and lack of understanding about Digital Rights are very important for the community on media social on the internet. Thus, the purpose of the filter with the theme of the role of human rights in the digital era is as a reminder, a support movement, or a symbol that human rights are still present even in the digital era. With the Visual Storytelling method to convey messages, philosophies, or stories through Instagram's AR filters. So that by using the visual storytelling method, it is hoped that the message to be conveyed about the importance of human rights. Through Instagram's AR filter, it can be more easily accepted and understood by the audience. Thus the use of the Visual storytelling method is very suitable for creating an Instagram AR filter work, the main thing of which is conveying messages to a broad audience, or public advertisements about the importance of Human Rights. So that by using the visual storytelling method, it is hoped that the message to be conveyed about the importance of human rights through the AR Instagram filter can be more easily accepted and understood by the audience. Because basically. Learning through visual media can make it easier for the audience to absorb, organize, and process information which will ultimately affect the achievement and learning of the audience.